Healthy Roots and Leaves: Comparative Genome Structure of Horseradish and Watercress - Mandáková, Terezie; Lysak, Martin A (Plant physiology, 2019)
Horseradish (Armoracia rusticana) and watercress (Nasturtium officinale) are economically important cruciferous vegetable species with limited genomic resources. We used comparative chromosome painting to identify the extent of chromosomal collinearity between horseradish and watercress, and to reconstruct the origin and evolution of the two tetraploid genomes (2n = 4x = 32). Our results show that horseradish and watercress genomes originated from a common ancestral (n = 8) genome, structurally resembling the Ancestral Crucifer Karyotype (n = 8), which, however, contained two unique translocation chromosomes (AK6/8 and AK8/6). Except for a 2.4-Mb unequal chromosome translocation in watercress, both genomes are structurally identical. The structural similarity of the two parental subgenomes might suggest an autotetraploid origin of horseradish and watercress genomes. The subgenome stasis, apart from the single-chromosome translocation, indicates that homeologous recombination played a limited role in postpolyploid evolution in both tetraploid genomes. The octoploid genome of one-rowed watercress (N. microphyllum, 2n = 8x = 64), structurally mirroring the tetraploid horseradish and watercress genomes, originated via autopolyploidization from the immediate tetraploid predecessor of watercress or hybridization between this and another now-extinct tetraploid Nasturtium species. These comparative cytogenomic maps in horseradish and watercress represent a first stepping stone for future whole-genome sequencing efforts and genetic improvement of both crop species.
Keywords: Homologous Recombination; molekulární evoluce; Tetraploidy; Genomics; Evolution, Molecular; Chromosomes, Plant; homologní rekombinace; Nasturtium; genom rostlinný; chromozomy rostlin; tetraploidie; karyotyp; Armoracia; Genome, Plant; genomika; Karyotype